2015
DOI: 10.1186/1866-1955-7-2
|View full text |Cite
|
Sign up to set email alerts
|

There is variability in the attainment of developmental milestones in the CDKL5 disorder

Abstract: BackgroundIndividuals with the CDKL5 disorder have been described as having severely impaired development. A few individuals have been reported having attained more milestones including walking and running. Our aim was to investigate variation in attainment of developmental milestones and associations with underlying genotype.MethodsData was sourced from the International CDKL5 Disorder Database, and individuals were included if they had a pathogenic or probably pathogenic CDKL5 mutation and information on ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
154
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 86 publications
(166 citation statements)
references
References 44 publications
(46 reference statements)
10
154
1
1
Order By: Relevance
“…Hence, every mutation was categorised into one of five groups according to the subsequent protein function: No functional protein; Missense/in-frame mutations within kinase domain; Truncations between aa172 and aa781; Truncations after aa781; and mutations that could not be grouped [8]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, every mutation was categorised into one of five groups according to the subsequent protein function: No functional protein; Missense/in-frame mutations within kinase domain; Truncations between aa172 and aa781; Truncations after aa781; and mutations that could not be grouped [8]. …”
Section: Methodsmentioning
confidence: 99%
“…Genotype-phenotype relationships have been difficult to study because of the paucity of recurrent mutations and the generally small case series. Our recent study ( n  = 127) which examined early development in this disorder categorised mutation types into four groups according to the effect on protein function and found that compared with those with no functional protein, those with a truncating mutation after amino acid (aa) 781 were more likely to acquire motor and communication skills [8]. …”
Section: Introductionmentioning
confidence: 99%
“…However, no information was provided on which seizure types responded to the KD, and overall the quality of the evidence was poor. 9,20 Methods The ICDD, established in 2012, collects information from caregivers of individuals with the CDKL5 disorder through either paper or online-based questionnaires, which families can complete at their own pace, or alternatively by telephone interview. 15 Early commencement of KD has also been associated with a good seizure response, especially in children with infantile spasms.…”
mentioning
confidence: 99%
“…Nevertheless, a recent randomized control trial reported improvements in seizure frequency and severity at 4 months when KD was prescribed in addition to regular AEDs. 7,9,20 The ICDD questionnaire was designed to capture comprehensive data pertaining to aspects of childhood development, phenotypic features, and natural history of the disorder. 16,17 This suggests potential therapeutic benefits in patients with the CDKL5 disorder, where seizure onset occurs early in infancy and includes infantile spasms in a substantial proportion.…”
mentioning
confidence: 99%
“…The CDKL5 protein C‐terminal region (amino acids 298‐1030) includes two putative nuclear localization signals NLS1 and NLS2 at positions (312‐315 aa) and (784‐789 aa) respectively, a nuclear export site (NES) at position (836‐845 aa). However, the hCDKL5_5 isoform contains the same domains as hCDKL5_1 to hCDKL5_4 isoforms but with an additional signal peptidase I serine active site (971‐978aa) (Hector et al, 2016; Fehr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%